The Literary type and irony writtinig In " Al-Kitab Amis Al-Makan AlAan" for Adonis - هاتف وتوت وداد; عبد الهادي المرهج سعيد (Al-Adab Journal, 2018)
The modernized creators have seen that the writing is an opened space , where they are permitted to accomplish their works away from the dominance of border and type . The theory of literary types has begun to retreat because the distinction among the literary types has been not considered of importance in writings of most our age writers. Does it consider rational that all literary types expressed by a human about his experiences and his secrets have been the same after huge development and changes got to the mind of a human and his nature ,his relations and his turning points. Why change in one type will be accepted , justified so long as it remains within the borders and within the sayings as to stretch the bridges of communication with others. This could be done by considering that the goal is the comprehension of a human experience. Thus, the writing has been replaced by the type as a ward for the self and as an assimilation to all dimensions of reality . The writing has become as an attraction to the intellectuality an as a set-off for selfness and as transparency for languages , getting away from renewal , its revolt against sameness , its conflict with the power . The writing has become as a space for all these aspects and for this reason, the modern writers have taken it as an intellectual creation that gives the creator huge capabilities that accomplish his visions and his creation extremely, as that it does mean ( breach, transgress, accomplishment , continued interaction, and interference) . This is the core of creation process.